Prevalence and Factors of Imposter Syndrome Among Health Science Students: A Scoping Review. - Judie, Erica L.; Kurszewski, Tammy R.; Case, Randy D. (Respiratory Care Education Annual)
Background: The aim of this scoping review is to analyze existing literature associated with imposter syndrome (IS) among students in health science studies, including graduate and undergraduate students, in order to identify the prevalence of IS occurrence, contributing factors, and opportunities for future research. Methods: A scoping literature review was conducted focusing on IS in health science students. Search terms were entered into PubMed, CINAHL, and Google Scholar without date or geographic restrictions. Two reviewers independently screened studies and identified 16 publications meeting the inclusion criteria. The authors independently performed qualitative and quantitative synthesis consistent with best practice recommendations for scoping reviews. Inclusion and exclusion criteria were determined through discussion. Included articles were summarized in a data extraction table for presentation in an understandable way (Appendix A). Results: Dependent on the screening tool and symptom assessment, prevalence rates of IS varied from 29.5% to 51%. Impostor syndrome was frequently observed in both men and women, although more predominantly in women. Impostor syndrome was also found to have a definitive correlation with psychological traits such as anxiety, depression, low self-esteem, poor self-efficacy, and perfectionism. Conclusions: IS is present and on the rise among health science students. An in-depth understanding of IS would provide guidance for faculty in health science education programs at both the undergraduate and graduate level.